KAJIAN PENGARUH SIKLON TROPIS MANGGA TERHADAP CURAH HUJAN, TRANSPOR EKMAN, VISKOSITAS EDDY DAN TINGGI GELOMBANG DI PERAIRAN SELATAN JAWA PADA 20-25 MEI 2020 - Satria Ginanjar; Muhammad Fikry Syach; Siti Wulandari (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
Tropical cyclone of Mangga formed on May, 20th – 25th 2020, located in southwest of Bengkulu, pricesly at coordinates of 9,8oS and 93,0oE over Indian Ocean Waters. This Cyclone does not cross Indonesia however can affect oceanographic parameters in Indonesia, notably on Southern Waters of Java . This study aims to determine changes in oceanographic parameters in the form of Ekman mass and volume transport, viscosity of Eddy and wave height during the Mangga Cyclone. The data used in reanalysis data extraction of surface wind direction and magnitude into wave height data, while Ekman transport and Eddy viscosity use combined surface wind data obtained from ERA5, also processed using IDL programming. The velocity of Mangga tropical cyclone became a tropical depression on May 19th 2020 was 14.07 m/s until its peak on May 20th, 2020 has maximum velocity at 14.07 m/s or 27.36 knots which has an impact on increasing Ekman transport velocity was 38,2 m2/s; Eddy’s mean viscosity was 23,36 m2/s; Rainfall mean was 165mm/day; and maximum wave height was 4.01 meters. These conditions also effect other oceanographic parameters and characteristic such as transformation of Eddy current patterns, upwelling events, and cooling sea surface temperatures (in combination with cloud cover effects) that occur during Mangga cyclone in the southern waters of Java.